2021
DOI: 10.3389/fnagi.2021.668948
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Age-Dependent Alterations in Excitability Properties of CA1 Pyramidal Neurons in an APPPS1 Model of Alzheimer’s Disease

Abstract: Age-dependent accumulation of amyloid-β, provoking increasing brain amyloidopathy, triggers abnormal patterns of neuron activity and circuit synchronization in Alzheimer’s disease (AD) as observed in human AD patients and AD mouse models. Recent studies on AD mouse models, mimicking this age-dependent amyloidopathy, identified alterations in CA1 neuron excitability. However, these models generally also overexpress mutated amyloid precursor protein (APP) and presenilin 1 (PS1) and there is a lack of a clear cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…The hyperexcitability in AD cells has also been previously linked to ion channel modifications (Chen, 2005; Beck and Yaari, 2008; Brown et al ., 2011; Zhang et al ., 2014; Kerrigan et al ., 2014; Liu et al ., 2015; Wang et al ., 2015b,a, 2016; Musial et al ., 2018; Ghatak et al ., 2019; Villa et al ., 2020; Vitale et al ., 2021; Müller et al ., 2021). Therefore, we explored which combination of these previously reported ion channel changes led to an increase of excitability in the APP/PS1 morphologies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The hyperexcitability in AD cells has also been previously linked to ion channel modifications (Chen, 2005; Beck and Yaari, 2008; Brown et al ., 2011; Zhang et al ., 2014; Kerrigan et al ., 2014; Liu et al ., 2015; Wang et al ., 2015b,a, 2016; Musial et al ., 2018; Ghatak et al ., 2019; Villa et al ., 2020; Vitale et al ., 2021; Müller et al ., 2021). Therefore, we explored which combination of these previously reported ion channel changes led to an increase of excitability in the APP/PS1 morphologies.…”
Section: Discussionmentioning
confidence: 99%
“…Our simulations showed that, although ion channel modifications alone led to an increased firing of especially bursts ( Supplementary Figure S4C , Middle panel ), they did not reproduce quantitatively the output mode transition from single spiking to predominantly burst firing as reported in figure 1B of (Šišková et al ., 2014). We tested also changes of other ion channels that have been linked to hyperexcitability including potassium, L-type calcium and hyperpolarisation-activated, cyclic nucleotide-gated HCN channels (Beck and Yaari, 2008; Musial et al ., 2018; Vitale et al ., 2021) but our simulations did not show a significant contribution to the increase in burst activity (see Methods).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations